2016
DOI: 10.1080/00380768.2016.1162110
|View full text |Cite
|
Sign up to set email alerts
|

Effects of organic fertilizer applications on starch changes in tobacco (Nicotiana tabacumL.) leaves during maturation

Abstract: Starch is a major feedstock for biofuel production. To meet growing fuel demands, the starch yields of energy crops need to be improved. In this study, the effects of the application of an organic fertilizer composed of cotton cake, oil cake and wheat straw at different concentrations (3000, 6000 and 9000 kg ha −1 ) were investigated in order to optimize the yield of tobacco (Nicotiana tabacum L.) leaves. To analyze the effects of the application of organic fertilizers on starch biosynthesis, we compared the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Higher plants, like maize, synthesize and store starch in the form of granules in storage tissues such as seeds, and in a temporary form in leaves, roots, and stems (Keeling and Myers, 2010;Song et al, 2016). Little starch is accumulated during the 'cell division' or endosperm differentiation phase (~10 DPA), which defines the final cell number of the grain (Altenbach et al, 2003).…”
Section: Resultsmentioning
confidence: 99%
“…Higher plants, like maize, synthesize and store starch in the form of granules in storage tissues such as seeds, and in a temporary form in leaves, roots, and stems (Keeling and Myers, 2010;Song et al, 2016). Little starch is accumulated during the 'cell division' or endosperm differentiation phase (~10 DPA), which defines the final cell number of the grain (Altenbach et al, 2003).…”
Section: Resultsmentioning
confidence: 99%
“…The absence of T 2 around 2 ms can be explained by lower starch content in young tobacco leaves, which were younger than the oilseed leaves studied. Indeed, Song et al [46] reported considerable variation in the amount of starch in leaves from young and mature tobacco plants. Using scanning electron microscopy, they observed that the volume of starch relative to the cell volume was less than 2% in leaves from the early mature plants (12th leaf rank at 70 DAS) and represented 15% in mature plants (at 100 DAS).…”
Section: Leaves At Two Developmental Stages Monitored Through Nmrmentioning
confidence: 99%
“…GO enrichment analysis indicated that topping would alter the expression of genes associated with starch metabolism and other biological processes. Starch content accounts for approximately 40% of the total dry weight of mature tobacco leaves (Song et al, 2016 ), and thus, the synthesis and conversion of starch are important factors in determining tobacco yields. Wang et al have reported that DEGs between topped and non‐topped tobacco are enriched in processes such as starch and sucrose metabolism (Wang et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%